Ventilation and Perfusion Lung Scintigraphy of Allergen-Induced Airway Responses in Atopic Asthmatic Subjects - Krishnan Parameswaran; Andrew C Knight; Niall P Keaney; E David Williams; Ian K Taylor (Canadian Respiratory Journal)
BACKGROUND: Both ventilation (V) and perfusion (Q) of the lungs are altered in asthma, but their relationships with allergen-induced airway responses and gas exchange are not well described.